Efficacy of acidified water-in-oil emulsions against desiccated Salmonella as a function of acid carbon chain-length and membrane viscosity - Chuang, Shihyu; Ghoshal, Mrinalini; McLandsborough, Lynne (Frontiers in Microbiology, 2023)
Sanitizing low-moisture food (LMF) processing equipment is challenging due to the increased heat resistance of Salmonella spp. in low-water activity (aw) environments. Food-grade oils mixed with acetic acid have been shown effective against desiccated Salmonella. In this study, different hydrocarbon chain-length (Cn) organic acids were tested against desiccated Salmonella by using 1% v/v water-in-oil (W/O) emulsion as the delivery system for 200 mM acid. Fluorescence lifetime imaging microscopy (FLIM) was utilized with a BODIPY-based molecular rotor to evaluate membrane viscosity under environmental conditions such as desiccation and temperature elevation. Drying hydrated Salmonella cells to 75% equilibrium relative humidity (ERH) increased the membrane viscosity from 1199 to 1309 mPa⋅s (cP) at 22 °C. Heating to 45 °C decreased the membrane viscosity of hydrated cells from 1199 to 1082 mPa⋅s, and decreased that of the desiccated cells from 1309 to 1245 mPa⋅s. At both 22 °C and 45 °C, desiccated Salmonella was highly susceptible (> 6.5 microbial log reduction (MLR) per stainless-steel coupon) to a 30-min treatment with the W/O emulsions formulated with short carbon chain acids (C1-3). By comparison, the emulsion formulations with longer carbon chain acids (C4-12) showed little to no MLR at 22 °C, but achieved > 6.5 MLR at 45 °C. Based upon the decreased Salmonella membrane viscosity and the increased antimicrobial efficacy of C4-12 W/O emulsions with increasing temperature, we propose that heating can make the membrane more fluid which may allow the longer carbon chain acids (C4-12) to permeate or disrupt membrane structures.